Cell Homogeneity Indispensable for Regenerative Medicine by Cultured Human Corneal Endothelial Cells - Hamuro, Junji; Toda, Munetoyo; Asada, Kazuko; Hiraga, Asako; Schlötzer-Schrehardt, Ursula; Montoya, Monty; Sotozono, Chie; Ueno, Morio; Kinoshita, Shigeru (Investigative Ophthalmology & Visual Science, 2016)
To identify the subpopulation (SP) among heterogeneous cultured human corneal endothelial cells (cHCECs) devoid of cell-state transition applicable for cell-based therapy.Subpopulation presence in cHCECs was confirmed via surface CD-marker expression level by flow cytometry. CD markers effective for distinguishing distinct SPs were selected by analyzing those on established cHCECs with a small cell area and high cell density. Contrasting features among three typical cHCEC SPs was confirmed by PCR array for extracellular matrix (ECM). Combined analysis of CD markers was performed to identify the SP (effector cells) applicable for therapy. ZO-1 and Na+/K+ ATPase, CD200, and HLA expression were compared among heterogeneous SPs.Flow cytometry analysis identified the effector cell expressing CD166+CD105-CD44- +/-CD26-CD24-, but CD200-, and the presence of other SPs with CD166+ CD105-CD44+++ (CD26 and CD24, either + or -) was confirmed. PCR array revealed three distinct ECM expression profiles. Some SPs expressed ZO-1 and Na+/K+ ATPase at comparable levels with effector cells, while only one SP expressed CD200, but not on effector cells. Human leukocyte antigen expression was most reduced in the effector SP. The proportion of effector cells (E-ratio) inversely paralleled donor age and decreased during prolonged culture passages. The presence of Rho-associated protein kinase (ROCK) inhibitor increased the E-ratio in cHCECs. The average area of effector cells was approximately 200 220 ?m2, and the density of cHCECs exceeded 2500 cells/mm2.A specified cultured effector cell population sharing the surface phenotypes with mature HCECs in corneal tissues may serve as an alternative to donor corneas for the treatment of corneal endothelial dysfunction.
EVALuna2:21305